A facile method for synthesizing polymeric nanofiber‐fragments. Issue 3 (19th July 2021) - Banerjee, Aihik; Jariwala, Tanvi; Kim, Sanggon; Tai, Youyi; Chiang, Sharon; Park, Honghyun; Myung, Nosang V.; Nam, Jin
Abstract: Electrospinning is a versatile method for synthesizing nanofibrous structures from nearly all polymers, offering a solution for the industrial‐scale mass production of nanomaterials in a wide range of applications. However, the continuous non‐woven structure intrinsic to electrospun fibers limits their applications, where a smaller length scale is desired. Here, we present a novel method to synthesize polymeric nanofiber‐fragments based on colloid electrospinning of polymer and sacrificial silica nanoparticles, followed by mechanical fracturing with ultrasonication. The size and hydrophobicity of silica nanoparticles are optimized for their improved integration within the polymer matrix, and the controllability of nanofiber‐fragment length by the amount of silica nanoparticle loading, down to 2 µm in length for poly(vinylidene fluoride‐trifluoroethylene) nanofibers with an average fiber diameter of approximately 100 nm, is shown. The resultant nanofiber‐fragments are shown to maintain their material properties including piezoelectric coefficients and their enhanced injectability for drug delivery application is demonstrated with an animal model. Abstract : Colloid electrospinning of polymer and sacrificial silica nanoparticles is utilized to synthesize polymeric nanofiber‐fragments. The resultant nanofiber‐fragments are shown to maintain their material properties and their enhanced injectability for drug delivery application is demonstrated.